Biodegradable polymeric nanoparticles administered in the cerebrospinal fluid: Brain biodistribution, preferential internalization in microglia and implications for cell-selective drug release. (July 2019) - Peviani, Marco; Capasso Palmiero, Umberto; Cecere, Francesca; Milazzo, Rita; Moscatelli, Davide; Biffi, Alessandra
Abstract: Cell-selective drug release in the central nervous system (CNS) holds great promise for the treatment of many CNS disorders but it is still challenging. We previously demonstrated that polymeric nanoparticles (NPs) injected intra-parenchyma in the CNS can be internalized specifically in microglia/macrophages surrounding the injection site. Here, we explored NPs administration in the cerebrospinal fluid (CSF) to achieve a wider spreading and increased cell targeting throughout the CNS; we generated new NPs variants and studied the effect of modifying size and surface charge on NPs biodistribution and cellular uptake. Intra-cerebroventricular administration resulted in prevalent localization of the NPs in proximity to stem-cell niches, such as around the lateral ventricles, the subventricular zone and the rostral migratory stream. NPs internalization occurred preferentially in brain myeloid cells/microglia. We demonstrated that brain biodistribution and extent of internalization in microglia are influenced by NPs dimensions and can be improved by applying a transient disruption of the blood-brain barrier with mannitol, leading to NPs internalization in up to 25% of brain myeloid/microglia cells. A fraction of the targeted cells was positive for markers of proliferation or stained positive for stemness/progenitor-cell markers such as Nestin, c-kit, or NG2. Interestingly, through these newly formulated NPs we obtained controlled and selective release of drugs otherwise difficult to formulate (such as busulfan and etoposide) to the target cells, preventing unwanted side effects and the toxicity obtained by direct brain delivery of the not encapsulated drugs. Overall, these data provide proof of concept of the applicability of these novel NP-based drug formulations for achieving internalization not only in mature microglia but also possibly in more immature myeloid cells in the brain and pave the way for brain-restricted microglia-targeted drug delivery regimens. Graphical abstract: Image 1